(untitled) (Communication & Society, 2023)
This study analyses temporary employees’ perceptions and experiences with respect to temporary employment companies (TECs), which contract them, and to the companies where they provide their services. Their level of possible integration in the strategies of employer branding in both types of companies is analysed. To that end, both the causes for their satisfaction or dissatisfaction with those companies have been studied and the temporary employee Net Promoter Score (eNPS) has been analysed in order to determine to what extent they may act as a company branding ambassador. This analysis has been carried out on the basis of two investigations conducted among employees from the same TEC before and after the Covid-19 pandemics, which has allowed us to count on a series of values to identify trends and, at the same time, to ascertain their impact on this type of employees caused by such a dramatic and global event as the recent pandemics started in 2020. With this in mind, we have reached a set of conclusions on how to improve the integration of this type of workers in companies through the improvement of internal communication and the strengthening of the corporative culture to foster their role as branding ambassadors in the companies where they operate.